VNAR: shark single-domain antibodies for the new era of medical biotechnology - Olivares-Olivares, Richard A.; Bravo, Angélica R.; Garrido-Soto, Carlos; Carvajal, Jonatan J.; Manubens, Augusto; Rivas, Mariella; Bustamente, Carlos; Retamal-Díaz, Angello; Kalergis, Alexis M.; Lay, Margarita K. (Frontiers in Immunology, 2026)
Shark-derived single-domain antibodies, known as VNARs, represent unique and advanced tools in medical biotechnology. Recognized for their small size, simple structure, and exceptional stability, VNARs can access cryptic epitopes that are inaccessible to traditional antibodies, making them valuable tools for next-generation diagnostic and therapeutic applications. Additionally, their evolutionary origin and structural diversity provide resistance to extreme pH, temperature, and proteolytic environments, making them especially suitable for demanding biomedical settings such as ocular and intestinal applications. Recent progress highlights their growing clinical potential: VNAR-based CAR-T cells targeting PD-L1 demonstrated strong anti-tumor effects in preclinical assays, with VNAR-B2 successfully blocking PD-L1/PD-1 interactions and reducing tumor growth in mouse models. Meanwhile, the TXB2 VNAR platform allows efficient, non-invasive transport of biologics across the blood-brain barrier. These developments emphasize VNARs’ advantages over traditional antibodies and even camelid VHHs in targeting difficult-to-reach sites and environments. Additionally, commercial development in VNAR technologies is advancing, with companies like Elasmogen using its soloMER™ platform to develop shark-derived, humanized single-domain antibodies for challenging therapeutic environments. This review consolidates emerging insights into VNAR structural biology, display technologies (phage, ribosome, yeast, and bacterial), and library engineering strategies, emphasizing their growing role in immunodiagnostics, infectious disease detection, targeted therapies, and barrier-crossing biologics. It addresses key translational challenges such as humanization and half-life extension, which are crucial for clinical application, ultimately highlighting the transformative potential of VNARs in bridging vital gaps in modern medicine.